Analisis Studi Kelayakan Rencana Pembangunan Tempat Pengolahan Sampah Terpadu (TPST) Kabupaten Kapuas Hulu, Provinsi Kalimantan Barat: Indonesia - A'fia, Khoiria; Putra, Hijrah Purnama; Yuriandala, Yebi; Wahyudi, Reza; Putranto, Rizky; Dewi, Kusmiyati (Asian Journal of Innovation and Entrepreneurship, 2026)
Population growth and increased activity have a direct impact on the increase in the amount and composition of waste produced by a region, requiring an effective and efficient waste management system. The development of an Integrated Waste Management Facility (TPST) is one alternative that can be implemented to address this issue. However, the construction of an ISWMP requires a significant investment, so it needs to be based on a comprehensive feasibility analysis in terms of environmental, technical, and economic aspects so that the facility can operate sustainably. This study aims to analyze this feasibility so that the ISWMP in Kapuas Hulu Regency can be built and operated until 2045. The methods used are population projection analysis until 2045, waste generation and composition projection analysis, assessment of alternative waste management technologies using a scoring method, and economic and financial feasibility analysis including Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), and Pay Back Period (PP). The analysis results show that the population of Kapuas Hulu Regency is projected to increase to 310,866 people by 2045, with waste generation reaching 57.95 tons/day. The composition of waste is dominated by food waste and plastic waste. Based on the technology scoring results, the recommended treatment system is a combination of BSF (Black Soldier Fly) maggots and Open Windrow composting for organic waste, Material Recovery Facility (MRF) for inorganic waste, and incineration for residual waste treatment. The economic and financial feasibility analysis shows that the TPST plan is feasible to implement, as indicated by an NPV > 0, an IRR of 112% exceeding the discount rate, a BCR > 1, and a PP shorter than the economic life of the plan. Based on these research results, the planning for the construction of the Kapuas Hulu Regency TPST is feasible from an economic and financial perspective and is therefore recommended as a long-term waste management solution.